Timestamp Representative of Weather Radar Images in the Cockpit. Issue 3 (2nd October 2019) - Hua, Lesheng; Ling, Chen; Thomas, Rick
ABSTRACT: Objective: The experiment reported here evaluated what a type of timestamp is an easy way for pilots to perceive and quickly assess the length of delay in NEXRAD mosaic radar images. Background: Data-linked mosaic NEXRAD images can be more than 14 min delayed by the time they reach the cockpit for use by pilots. The NTSB issued a safety alert to warn that the NEXRAD "age indicator" can be misleading. Unfortunately, research has indicated that pilots may not be fully aware of the delay and that it can adversely affect their decision-making and performance. Method: The three types of timestamps were "direct age", "clock", and "UTC" with three levels of time delay (short, medium, and long). Twenty-one participants read and compared two radar images, via timestamps, to determine the length of delay and which one was more recent. Results: The results indicated that the type of timestamp and the length of time delay significantly affected participants' response time and accuracy. "UTC" timestamp with a long-time delay was associated with the longest response time and low accuracy. The "direct age" timestamp led to the highest accuracy and shortest response time for all manipulated levels of time delay. Conclusion: Although "UTC" format is commonly used in many weather products, we found the "direct age" format to be the superior method to support perceptions of time delay.